2020
DOI: 10.3390/ijms21020656
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analyses of Cytochrome P450 Monooxygenases and Secondary Metabolite Biosynthetic Gene Clusters in Cyanobacteria

Abstract: The prokaryotic phylum Cyanobacteria are some of the oldest known photosynthetic organisms responsible for the oxygenation of the earth. Cyanobacterial species have been recognised as a prosperous source of bioactive secondary metabolites with antibacterial, antiviral, antifungal and/or anticancer activities. Cytochrome P450 monooxygenases (CYPs/P450s) contribute to the production and diversity of various secondary metabolites. To better understand the metabolic potential of cyanobacterial species, we have car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(62 citation statements)
references
References 80 publications
1
59
0
Order By: Relevance
“…3). Cyanobacterial species also had no P450 family conserved, but P450 families CYP110 and CYP120 were found to be a co-presence in www.nature.com/scientificreports/ www.nature.com/scientificreports/ most of these species 49 . the large CYP107 family was found to be conserved in Streptomyces species 46 and quite a number of P450 families were found to be conserved in mycobacterial species 47 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3). Cyanobacterial species also had no P450 family conserved, but P450 families CYP110 and CYP120 were found to be a co-presence in www.nature.com/scientificreports/ www.nature.com/scientificreports/ most of these species 49 . the large CYP107 family was found to be conserved in Streptomyces species 46 and quite a number of P450 families were found to be conserved in mycobacterial species 47 .…”
Section: Resultsmentioning
confidence: 99%
“…Studies on the role of P450s in organism's adaptations or changes in P450 profiles according to an organism's life have been conducted on eukaryotic organisms such as fungi [34][35][36][37][38][39][40][41] , oomycetes 42 , plants 43 , and animals 44 . However, this phenomenon is scarcely reported in prokaryotes; currently data are available only for bacterial species belonging to the genera Streptomyces 45,46 , Mycobacterium 47,48 and the phylum Cyanobacteria 49 , suggesting that more research is needed to unravel P450s' role in other bacterial species. The presence of species with diverse characteristics that are adapted to diverse ecological niches, such as in Firmicutes, will enhance understanding of the role of P450s in bacterial species, especially with respect to their role in those organism's adaptations.…”
mentioning
confidence: 99%
“…Analysis of the most prevalent number of P450s revealed that 19 P450s was the prevalent number in Streptomyces species ( Table 1 ). The average number of P450s in Streptomyces species was found to be higher than in Bacillus species [ 22 ] and cyanobacterial species [ 23 ], and almost the same as in mycobacterial species [ 21 ] ( Table 2 ). A point to be noted is that the number of species greatly influences the average number of P450s and, thus, the higher the number of species in the analysis, the better and more accurate the results, as mentioned elsewhere [ 20 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…P450s in the newly sequenced species need to be annotated as per the International P450 Nomenclature Committee rules [ 17 , 18 , 19 ] to enable researchers to use the same names for functional and evolutionary analysis of P450s. For this reason, large numbers of P450s have recently been annotated in bacterial species belonging to the genera Mycobacterium [ 21 ], Bacillus [ 22 ], Streptomyces [ 20 ], and Cyanobacteria [ 23 ]. These studies have revealed numerous P450s involved in the synthesis of different types of secondary metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…Another metabolically important enzyme, upregulated in the presence of BMAA, was identified as Cytochrome P450 ( all1361 ) ( Table 2 ). It is known that Cytochrome P450 monooxygenases (CYPs/P450s) is a diverse superfamily of heme-dependent enzymes that contribute to the production and diversity of various secondary metabolites and are present in all cyanobacteria [ 61 ]. These enzymes introduce oxygen into a wide range of molecules.…”
Section: Resultsmentioning
confidence: 99%